Agreement on diabetic retinopathy grading in fundus photographs by allied ophthalmic personnel as compared to ophthalmologist at a community setting in Nepal - Thapa, Raba; Bajimaya, Sanyam; Pradhan, Eli; Paudyal, Govinda (Nepalese Journal of Ophthalmology, 2017)
Introduction: Diabetic retinopathy (DR) is the emerging cause of blindness in the developing world. Timely detection of DR could save vision from its avoidable blinding condition. Objective: To assess the accuracy of DR grading in fundus photographs by the allied ophthalmic personnel (AOP) as compared to ophthalmologist at a community setting in Nepal. Materials and methods: Fundus photographs of known diabetes subjects attending for DR screening were graded by two groups of AOP and ophthalmologist. Agreement for DR grading by the AOP versus ophthalmologist was assessed using kappa coefficient (k). Results: Fundus photographs of 864 eyes of 435 subjects with diabetes were evaluated in the study. The agreement was substantial for detection of normal versus abnormal retina by both the AOP 1 and AOP 2. For normal versus abnormal macula, the agreement was substantial for AOP 1 and moderate for AOP 2. The agreement for grading macular exudates, retinal hemorrhage, venous beading ranged from moderate to substantial for both the AOPs. There was overall substantial agreement for diagnosing cases with or without DR and CSME by both the AOP 1 and AOP 2. The agreement ranged from fair to moderate for diagnosing other stages of NPDR by both the AOPs. Conclusion: Allied ophthalmic personnel with training could be a first level DR screener and referral of vision threatening DR. Three out of five diabetics could be managed at community level and thus reduce work load of ophthalmologist. This DR screening modality can be useful in other resource limited countries.